MALIGNANT SCHWANNOMA IN NEUROFIBROMATOSIS1 - S., PEUNGJESADA; A., CHUROJANA; P., CHIEWVIT; S., BENAJARASSAMEROTe; A., ASAVAMONGKOLKUL (The ASEAN Journal of Radiology, 2023)
Malignant peripheral nerve sheath neoplasms are serious complications of Neurofibromatosis. The incidence of which reported in literatures is between 2% and 29%. Once it occurs, the prognosis is poor. We reviewed 2 cases of malignant schwannoma in the vicinity of Neurofibromatosis-1 at Siriraj Hospital in the points of view of radiographic findings with histopathological correlations. One had lesion at chest wall and the other at sacral area. Both CT and MRI provided good structural delineation and tumor extension but malignant or benign lesions can not be distinguished with certainty. Because of its aggressiveness, biopsy with histological diagnosis should be performed in those Neurofibromatosis patients who have peripheral nerve sheath tumors before surgical planning. Malignant degeneration of peripheral nerve sheath tumors 1s problematic in NF-1 patients. Its incidence has been estimated to be 2-29 %1 or 10 to 10,000 times more than general population.2 Spontaneous sarcomatous change in patients without von Recklinghausen ‘s disease is very rare.3 It has poor prognosis1,4-9 and causes high morbidity and mortality. Early recognition of this change brings about early treatment and greater awareness. But they are difficult to be differentiated from benign neoplasm.10 Because they can produce no symptom, either, mild or aggressive symptoms.3,10 There is no imaging criteria for differentiation malignant from benign tumor.10 This study was performed retrospectively to determine if CT scans and MR imaging would be any useful for distinguishing malignant from benign neoplasms. Pathological findings and correlation between pathology and radiology were also analyzed.